2002
DOI: 10.1021/bi025822i
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Bonding to P700:  Site-Directed Mutagenesis of Threonine A739 of Photosystem I in Chlamydomonas reinhardtii,

Abstract: The primary electron donor P700 of photosystem I is a dimer comprised of chlorophyll a (P(B)) and chlorophyll a' (P(A)). P(A) is involved in a hydrogen bond network with several surrounding amino acid residues and a nearby water molecule. To investigate the influence of hydrogen bond interactions on the properties of P700, the threonine at position A739, which donates a putative hydrogen bond to the 13(1)-keto group of P(A), was replaced with valine, histidine, and tyrosine in Chlamydomonas reinhardtii using s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
111
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(130 citation statements)
references
References 52 publications
17
111
2
Order By: Relevance
“…The intensity of the ∼680-nm band was somewhat variable and usually larger in particles (data not shown); it may contain contributions from bleached antenna chlorophylls. These results are in good agreement with those obtained previously by Witt et al (16) in both spectral regions. However, we note that the additional bleaching band at ∼678 nm is smaller in our mutant than in any of theirs.…”
Section: Figure 3: P 700supporting
confidence: 94%
See 1 more Smart Citation
“…The intensity of the ∼680-nm band was somewhat variable and usually larger in particles (data not shown); it may contain contributions from bleached antenna chlorophylls. These results are in good agreement with those obtained previously by Witt et al (16) in both spectral regions. However, we note that the additional bleaching band at ∼678 nm is smaller in our mutant than in any of theirs.…”
Section: Figure 3: P 700supporting
confidence: 94%
“…However, we note that the additional bleaching band at ∼678 nm is smaller in our mutant than in any of theirs. Because the relative size of this band seems to decrease from the T739Y to the T739V mutant (16), it may be related to the strength of hydrogen bonding to P A . This is consistent with the claim that the T739A mutant has the most severe effect (see below).…”
Section: Figure 3: P 700mentioning
confidence: 97%
“…3, spectrum C), showing a strong decay of the emissive compared with the enhanced absorptive signals, suggests that the emissive signals originate from the donor Chl. The emissive signal at 211.5 ppm is broadened by a shoulder at Ϸ215 ppm (Table 1), indicating involvement of a second donor Chl cofactor, which can be due to the epimerization at the C-13 2 and the different hydrogen-bonding at the 13 1 -keto group (21), causing also the split of the N-IV signal (250.3 and 254.9 ppm), whereas no effect is observed on the remote N-I position (186.2 ppm). The resonance of N-III is observed at 193.2 ppm.…”
Section: Resultsmentioning
confidence: 99%
“…Two mechanisms could account for the lowered frequency: (1) the 13 3 ester CdO is coupled to the bridging ester oxygen, which is H-bonded ( Figure 2C). We note, however, that the ester oxygen is likely to be a weak H-bond acceptor (11). (2) The lowered frequency of the 13 3 ester CdO of P A could also result from the fact that P A is a Chla′ and/or the fact that ring V of P A (unlike P B ) is considerably bent out of the plane of the macrocycle ( Figure 2C,F).…”
Section: Discussionmentioning
confidence: 99%
“…However, this is likely to be the case only if an H-bond to the 13 1 keto CdO of P A is still present in the TA(A739) mutant. Witt et al have also concluded that an H-bond is still present in all three of their TA739 mutants (11). The H-bond in the mutant is possibly mediated by an introduced water molecule.…”
Section: In the Ftir Ds Inmentioning
confidence: 93%